2006
DOI: 10.1089/dia.2006.8.627
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Continuous Real-Time Blood Glucose Monitoring During and After Prolonged High-Intensity Cycling Exercise: Spinning with a Continuous Glucose Monitoring System

Abstract: These limited data suggest that nocturnal LOH occurs commonly following vigorous exercise and that a Guardian RT is a useful and important diagnostic tool. Further study into clinical strategies for preventing hypoglycemia associated with this common form of mixed aerobic and anaerobic exercise is urgently needed through insulin modification and carbohydrate supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 23 publications
6
69
1
3
Order By: Relevance
“…26 During moderate-intensity exercise lag times of up to 20 min were observed with the Guardian Ò REAL-Time (Medtronic MiniMed), 14 compared with only 8-12 min at rest for the next-generation EnliteÔ sensor (Medtronic MiniMed). 27 The DexCom Ò (San Diego, CA) and FreeStyle Navigator CGM devices report similar lag times (6 and 13 min, respectively) under sedentary conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 During moderate-intensity exercise lag times of up to 20 min were observed with the Guardian Ò REAL-Time (Medtronic MiniMed), 14 compared with only 8-12 min at rest for the next-generation EnliteÔ sensor (Medtronic MiniMed). 27 The DexCom Ò (San Diego, CA) and FreeStyle Navigator CGM devices report similar lag times (6 and 13 min, respectively) under sedentary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] The study was carried out in a carefully controlled clinical research facility setting, over a 22.5-h duration, thus providing numerous paired glucose values for analysis. We used plasma glucose measured by the YSI 2300 STAT Plus analyzer as the reference standard, unlike other studies that used capillary glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hypoglycemia during just one 75-min intermittent exercise session occurred in 86% of children starting the exercise with normal glucose levels (Tansey et al 2006). In studies of adults with type 1 diabetes who had continuous glucose monitoring, nearly all active persons were shown to develop exercise-associated hypoglycemia within 12-24 h of recovery (Iscoe et al 2006(Iscoe et al , 2008 . In a multicentered study of 50 youth with type 1 diabetes, postexercise hypoglycemia occurred in 26% of subjects after just 1 typical exercise bout, compared with only 6% in the same children after a sedentary day (Tsalikian et al 2005).…”
Section: Risks Of Exercise In Type 1 Diabetesmentioning
confidence: 99%
“…9,10 Exercise has also been shown to mask hypoglycemic symptoms, facilitating repeated exposure to unrecognized hypoglycemia and potentially causing hypoglycemia-associated autonomic failure 7 with all its negative consequences. 11,12 Recent closed-loop control artificial pancreas (AP) studies have shown reduction in the risk for hypoglycemia in T1DM subjects, increase of the time in near-normoglycemia (70-180 mg/dL), and reduction in average glucose level, both in the hospital and in home-like settings, with and without exercise. [13][14][15][16][17][18][19][20][21][22] However, although overnight hypoglycemia can be reduced severalfold, preventing hypoglycemia during and immediately after exercise remains a hurdle, likely due to the inherent delay of the glycemic response to exercise coupled with delays due to subcutaneously injected insulin.…”
mentioning
confidence: 99%